PERAN IMAM MADZHAB DAN INTERAKSI SOSIAL DALAM PENERAPAN HUKUM ISLAM - Abdul Wasik (Al'Adalah, 2015)
Fiqh is not Al-Quran and Al-Hadith that we can not change tenses and its meaning, but fiqh only an ijtihad product and that the priests schools whose source is taken from the Quran and Al-Hadith. Likewise fiqh is not filled with the teachings of the monotheistic doctrine, but it elastic and dynamic in its application. The fall of the Qur'an, or better known and the emergence of Al-Hadith in Mecca and Madina are very different situations and conditions with Indonesia. The legal rulings product that was born when the course is also different from the product that appears on Indonesian fiqh. One reason is the social interaction and the circumstances that exist, thereby causing product also different fiqh law.